Factors Affecting Nurses’ Motivation And Confidence For Increased Self-Regulated And Collaborative Learning In Second Life Environment - Khaleel, Ahmed Isam (2017)
This study was conducted to investigate the potential use of Second Life (SL) to facilitate student nurses’ confidence and motivation, as well as its impact on their self-regulated and collaborative learning development. To build the SL environment, instructional design model of Dick and Carey was used to design the two learning scenarios of LifePak Defibrillator and anaesthesia machine. A quantitative research approach employing the survey method was used in this study. A model fit for Partial Least Squares (PLS) – Structural Equation Modeling (SEM) technique on 218 participants was produced to estimate the direct effect of environmental elements in terms of environment content design (ECD), environment interactivity (EI), and environment functionality (EF) on student nurses’ behaviour in terms of motivation and confidence.